Misbehaving: The Making of Behavioral Economics - Thalar, Richard H. (UK Penguin Random House, 2015)
Shortlisted for the Financial Times & McKinsey Business Book of the Year Award. Get ready to change the way you think about economics. Richard H. Thaler has spent his career studying the radical notion that the central agents in the economy are humans$1 (Bpredictable, error-prone individuals. Misbehaving is his arresting, frequently hilarious account of the struggle to bring an academic discipline back down to earth$1 (Band change the way we think about economics, ourselves, and our world. Traditional economics assumes rational actors. Early in his research, Thaler realized these Spock-like automatons were nothing like real people. Whether buying a clock radio, selling basketball tickets, or applying for a mortgage, we all succumb to biases and make decisions that deviate from the standards of rationality assumed by economists. In other words, we misbehave. More importantly, our misbehavior has serious consequences. Dismissed at first by economists as an amusing sideshow, the study of human miscalculations and their effects on markets now drives efforts to make better decisions in our lives, our businesses, and our governments. Coupling recent discoveries in human psychology with a practical understanding of incentives and market behavior, Thaler enlightens readers about how to make smarter decisions in an increasingly mystifying world.s
Keywords: BUSINESS & ECONOMICS -- Consumer Behavior; Psychological aspects; Economics